2020
DOI: 10.1109/access.2020.2977962
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ovarian Tumors in Obstetric Ultrasound Imaging Using Logistic Regression Classifier With an Advanced Machine Learning Approach

Abstract: This paper addresses the use in different stages of pregnancy of ultrasound imaging and to examine the tumors diagnosed during lactation or pregnancy. There are recent advancements in the application of obstetric ultrasound and imaging techniques helpful for improving the outcome of the pregnancy using various Learning techniques. This paper addresses the need to implement sustainable ultrasound standards with an acceptably high maternal and perinatal mortality rates to provide better and more affordable, qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The proposed method is compared with other methods to accomplish its algorithm verification, which further illustrates the effectiveness and scalability of the proposed method. The regression algorithms involved in the comparison include logistic regression [37], SVM [38][39], random forest [40][41], SGD and the proposed method. The constructed model is shown in Fig.…”
Section: F Methods Comparison and Verificationmentioning
confidence: 99%
“…The proposed method is compared with other methods to accomplish its algorithm verification, which further illustrates the effectiveness and scalability of the proposed method. The regression algorithms involved in the comparison include logistic regression [37], SVM [38][39], random forest [40][41], SGD and the proposed method. The constructed model is shown in Fig.…”
Section: F Methods Comparison and Verificationmentioning
confidence: 99%
“…(4) More test data for different time periods than in this study can be used for further reverifying the study performance. (5) The inclusion of additional evaluation criteria is a requirement for further measuring the proposed model. ( 6) Other potential models can be organized with the proposed hybrid model to further measure and test the proposed model.…”
Section: Future Researchmentioning
confidence: 99%
“…Furthermore, from the limited examples of extensive literature reviews on data mining techniques, it is found that some effective classifiers (or called models) have emerged in various application fields and become popular among practitioners and academics due to their superior performance in the past few decades. These classifiers (algorithms), such as Naive Bayes (NB) [4], logistic (LG) [5], K-nearest neighbor (KNN) [6], bagging (BAG) algorithm [7], and decision trees (DTs) [8], also have good application performance in financial domains; thus, they are selected for use in this study. Moreover, the well-known Altman Z-score model [9] is ever emphasized for such financial predictions as bankruptcy of stock market, and it also provides outstanding results; at the same time, the logistic regression (LR) method [10] is also a helpful technique designed for identifying classification models for financial datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, all these devices optimized for the daily clinical routine (or for home-care settings in the case of DFree or SENS-U) are difficult to utilize in research applications, where customized signal and image processing algorithms need to be applied to the data. In particular, machine-learning based approaches have been shown to have tremendous potential for automated segmentation of ultrasound data [ 10 ], and have been reported in particular for breast imaging [ 11 ], coronary arteries [ 12 ], and thyroid [ 13 ] or different tumors [ 14 ]. In comparison to these applications, where the anatomy is more complex and the contrast difference is reduced, bladder segmentation represents an ideal use case for ML-based approaches due to the low echogenity and the resulting high contrast to surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%